Advanced modelling of commuter choice model and work from home during COVID-19 restrictions in Australia. (June 2022) - Balbontin, Camila; Hensher, David A.; Beck, Matthew J.
Highlights: Understand underlying attitudes in the decision to WFH or to commute during COVID. Two latent variables: concern towards the use of PT and attitude towards WFH. Occupation or income have a high influence on WFH, relative to travel times. PT concern is moderated by regular and reliable services. Balance between WFH and office is preferred. Abstract: The decision to work from home (WFH) or to commute during COVID-19 is having a major structural impact on individuals' travel, work and lifestyle. There are many possible factors influencing this non-marginal change, some of which are captured by objective variables while others are best represented by a number of underlying latent traits captured by attitudes towards WFH and the use of specific modes of transport for the commute that have a bio-security risk such as public transport (PT). We develop and implement a hybrid choice model to investigate the sources of influence, accounting for the endogenous nature of latent soft variables for workers in metropolitan areas in New South Wales and Queensland. The data was collected between September-October 2020, during a period of no lockdown and relatively minor restrictions on workplaces and public gatherings. The results show that one of the most important attributes defining the WFH loving attitude is the workplace policy towards WFH, with workers that can decide where to work having a higher probability of WFH, followed by those that are being directed to, relative to other workplace policies. The bio-security concern with using shared modes such as public transport is a key driver of WFH and choosing to commute via the safer environment of the private car.